(untitled) (REMUNOM, 2026)
Honey is a product of animal origin, produced by honeybees from flower nectar and other plant secretions, which they collect and mature in the combs of their hives. Honey is widely consumed in Brazil and worldwide, both directly and indirectly, through many therapeutic and/or food products, such as mead, a fermented beverage obtained from bee honey, with or without the addition of agents that impart a specific flavor and aroma. The present work aimed to prepare a mead from bee honey of the Apis mellífera species, originating from a municipality in Pará, flavored with jambu flowers (Acmella oleracea), in two different formulations, according to the mass of jambu flower used, and to characterize the meads prepared from a physicochemical point of view, in addition to verifying the influence of the formulations on the physicochemical properties of the drinks produced. Established methodologies were used to determine pH, electrical conductivity, acidity, moisture, density, total soluble solids, ratio, viscosity, and alcohol content. Measurements were performed in triplicate for each sample and variable studied. The raw materials used, that is, honey and jambu flowers, presented good physicochemical quality and the three meads produced also presented good physicochemical quality, being drinks of high acidity, with pH between 3.78 and 3.99, which contributes to their stability against microorganisms, low alcohol content (between 8% and 10%), low viscosity (between 519.41 cSt and 340.00 cSt) and total soluble solids content (TSS) between 14.00º Brix and 18.53º Brix, therefore not being overly sweet drinks, which is confirmed by their ratios found, between 0.32 and 1.46. The investigated variables presented variation in their physicochemical properties according to the product formulation, and the three formulations can be considered of good physicochemical quality.